Fabricate 2014 (UCL Press, 2017)
FABRICATE is an international peer reviewed conference that takes place every three years with a supporting publication on the theme of Digital Fabrication. Discussing the progressive integration of digital design with manufacturing processes, and its impact on design and making in the 21st century, FABRICATE brings together pioneers in design and making within architecture, construction, engineering, manufacturing, materials technology and computation. Discussion on key themes includes: how digital fabrication technologies are enabling new creative and construction opportunities from component to building scales, the difficult gap that exists between digital modelling and its realisation, material performance and manipulation, off-site and on-site construction, interdisciplinary education, economic and sustainable contexts. FABRICATE features cutting-edge built work from both academia and practice, making it a unique event that attracts delegates from all over the world.